PENGARUH UMUR BETON TERHADAP KUAT TEKAN BETON AKIBAT PENAMBAHAN ABU CANGKANG LOKAN - Fepy Supriyani (Inersia: Jurnal Teknik Sipil, 2019)
The sea-shell ash content high of calsium carbonate, if heated in controlled temperature will be contain a calcium, as substitute a part of cement. One of the sea-shell type in Bengkulu town is lokan shell which the contents taken to be eat and the shell become waste. This research will exploit sea-shell ash which added as concrete mixture to see develop of concrete compressive strength at early age and after 28 day. The concrete mix design use fas 0,5 and slump 60-100 cm. Used 140 silinder sample, dimension 15 cm diameter and 30 cm heigh.Percentage of addition of sea shell ash is 2,5%, 5%, and 10% from cement weight. Test parameter included compressive strength test at the age of 3, 7, 14, 28, 56 days, 120 day ( 3 months) and 180 day (6 months). The result is at early age the concrete strength is not significantly affected when concrete is added by 2,5% and 10% of the mixture of sea-shell ash, in addition 5% sea shell bigger than concrete without sea shell ash. In addition 5% sea shell ash can improve concrete strength after 28 day, and reach optimum value at age 180 day is 49,42 Mpa , strong depress concrete.